Smart dynamic hybrid membranes with self-cleaning capability - Pantuso, Elvira; Ahmed, Ejaz; Fontananova, Enrica; Brunetti, Adele; Tahir, Ibrahim; Karothu, Durga Prasad; Alnaji, Nisreen Amer; Dushaq, Ghada; Rasras, Mahmoud; Naumov, Panče; Di Profio, Gianluca (Nature communications, 2023)
The growing freshwater scarcity has caused increased use of membrane desalination of seawater as a relatively sustainable technology that promises to provide long-term solution for the increasingly water-stressed world. However, the currently used membranes for desalination on an industrial scale are inevitably prone to fouling that results in decreased flux and necessity for periodic chemical cleaning, and incur unacceptably high energy cost while also leaving an environmental footprint with unforeseeable long-term consequences. This extant problem requires an immediate shift to smart separation approaches with self-cleaning capability for enhanced efficiency and prolonged operational lifetime. Here, we describe a conceptually innovative approach to the design of smart membranes where a dynamic functionality is added to the surface layer of otherwise static membranes by incorporating stimuli-responsive organic crystals. We demonstrate a gating effect in the resulting smart dynamic membranes, whereby mechanical instability caused by rapid mechanical response of the crystals to heating slightly above room temperature activates the membrane and effectively removes the foulants, thereby increasing the mass transfer and extending its operational lifetime. The approach proposed here sets a platform for the development of a variety of energy-efficient hybrid membranes for water desalination and other separation processes that are devoid of fouling issues and circumvents the necessity of chemical cleaning operations. The performance of membrane desalination of seawater is hampered by fouling. Here the authors develop smart gating hybrid membranes by surface coating with polymer-embedded thermosalient crystals. These membranes enhance pure water flux by over 40% in saltwater desalination by osmotic distillation.